Faster parameterized algorithms for variants of 3-Hitting Set - Tsur, Dekel (Journal of combinatorial optimization, 2025)
In the A -Multi 3 -Hitting Set problem ( A -M3HS), where A ⊆ { 1 , 2 , 3 } , the input is a hypergraph G in which the hyperedges have sizes at most 3 and an integer k , and the goal is to decide if there is a set S of at most k vertices such that | S ∩ e | ∈ A for every hyperedge e . In this paper we give O ∗ ( 2 . 027 k ) -time algorithms for { 1 } -M3HS and { 1 , 3 } -M3HS, and an O ∗ ( 1 . 381 k ) -time algorithm for { 2 } -M3HS.